2017
DOI: 10.1002/ente.201700308
|View full text |Cite
|
Sign up to set email alerts
|

Effect of TiO2 Surface Treatment on the Current–Voltage Hysteresis of Planar‐Structure Perovskite Solar Cells Prepared on Rough and Flat Fluorine‐Doped Tin Oxide Substrates

Abstract: Herein,w es tudiedt he effect of surface treatment of compact TiO 2 layer by vacuum ultraviolet (VUV) light and by TiCl 4 on the I-V hysteresis of perovskite solar cells prepared on fluorine-dopedt in oxide (FTO) substrates with two different surface roughnesses.I nitially,t he cells prepared on flat FTO substrates show better results than cells prepared on rough FTO,w ith slightly higher power conversione fficiency (PCE) and less hysteresis in the I-V curves.T reatment of TiO 2 preparedo nf lat FTO has no eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 21 publications
2
22
0
Order By: Relevance
“…For the bare FTO, the average surface roughness was ca. 27.50 nm, which is consistent with the reported value [32]. The particle size of the FTO was in the range from ten to several hundred nanometers, which is advantageous to obtain a high density of CYS-SAM onto the FTO electrode.…”
Section: Contact-angel and Afm Characterizations Of Cys-samsupporting
confidence: 90%
“…For the bare FTO, the average surface roughness was ca. 27.50 nm, which is consistent with the reported value [32]. The particle size of the FTO was in the range from ten to several hundred nanometers, which is advantageous to obtain a high density of CYS-SAM onto the FTO electrode.…”
Section: Contact-angel and Afm Characterizations Of Cys-samsupporting
confidence: 90%
“…Recently, research direction has been focused on the slow processes occurring in the PSCs to study possible cause of hysteresis. The charge accumulation at the TiO 2 /perovskite interface coupled with ionic migration may cause this phenomenon [ 23 , 30 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results showed an increment in PCE, mostly due to better charge extraction after modifying the TiO 2 layer. Following a similar strategy, Cojocaru et al [ 30 ] carried out a post-treatment to the blocking TiO 2 layer with TiCl 4 and demonstrated an efficiency enhancement of 3% when comparing reverse- versus forward-measurement directions. In a similar fashion, Grätzel et al [ 31 ] and Friend et al [ 32 ] demonstrated beneficial effects when mesoporous TiO 2 is post-treated with Li 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…The perovskite precursor solution was prepared by dissolving methylammonium iodide and lead (II) chloride in 3:1 molar ratio in 700 μL of DMF and stirring for 1 hr at 70 °C. This suspension was then spin coated onto the TiO 2 porous layer at 2000 rpm for 30 s [35]. It was then sintered at 120 °C for 45 min.…”
Section: Methodsmentioning
confidence: 99%
“…1 mL of 97 mg/mL spiro-OMeTAD in chlorobenzene mixed with 30.2 µL of 175 mg/mL Bis(trifluoromethane) sulfonamide lithium salt in acetonitrile and 9.7 µL of solution consists of 46.6% of 4-tert-butylpyridine in acetonitrile. This mixed solution was spin coated on the perovskite film at 2000 rpm for 30 s [35]. Finally, 80 nm Au electrode was deposited on spiro-OMeTAD coated devices by thermal evaporation at a constant evaporation rate of 0.2 Å/s under 1 × 10 −6 torr vacuum.…”
Section: Methodsmentioning
confidence: 99%